LG in India (C) : sustaining competitive advantage - Salwan, Prashant (London : NeilsonJournals Publishing, 2011)
LG was market leader in nearly all its product lines and segments in consumer electronics in India in 2007. LGIL had appointed a new MD who had to develop strategies to enable the company to sustain its market position. This case details the distribution, product development and service focus of LG, together with changing consumer behavior up to the present time with projections for strategy into the future.
Originally Published InSalwan, P. (2011). LG in India (C): Sustaining competitive advantage. Journal of International Business Education, 6(1), 77-94. JIBE6-0CS3.
Description based on XML content.
Keywords: elektronické knihy; electronic books; LG Cho?nja (Korea) -- Management -- Case studies; International business enterprises -- Management -- Case studies; Electronic industries -- India -- Case studies; Electronic industries -- Korea -- Case studies; Product management -- Case studies; New products -- Case studies